2009 IEEE International Symposium on Workload Characterization (IISWC) 2009
DOI: 10.1109/iiswc.2009.5306783
|View full text |Cite
|
Sign up to set email alerts
|

Phoenix rebirth: Scalable MapReduce on a large-scale shared-memory system

Abstract: Abstract-Dynamic runtimes can simplify parallel programming by automatically managing concurrency and locality without further burdening the programmer. Nevertheless, implementing such runtime systems for large-scale, shared-memory systems can be challenging. This work optimizes Phoenix, a MapReduce runtime for shared-memory multi-cores and multiprocessors, on a quad-chip, 32-core, 256-thread UltraSPARC T2+ system with NUMA characteristics. We show how a multi-layered approach that comprises optimizations on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(132 citation statements)
references
References 11 publications
0
129
1
2
Order By: Relevance
“…Cilk offers a simple means to express parallel loops (using the cilk_for syntax) and reductions (using generalized reducer hyperobjects [11]). These two concepts have the same conceptual programming complexity as other map-reduce systems [26], [27], [31], [33], [35]. CilkMR, however, retains the structure of the sequential code, which is in stark contrast to previously proposed map-reduce frameworks.…”
Section: Introductioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Cilk offers a simple means to express parallel loops (using the cilk_for syntax) and reductions (using generalized reducer hyperobjects [11]). These two concepts have the same conceptual programming complexity as other map-reduce systems [26], [27], [31], [33], [35]. CilkMR, however, retains the structure of the sequential code, which is in stark contrast to previously proposed map-reduce frameworks.…”
Section: Introductioncontrasting
confidence: 42%
“…Yoo et al [35] improved the scalability of Phoenix for a 256-thread SPARC T2 machine. They found that the internal data structures that store intermediate data are critical for performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alternative hardware environments, such as a shared-memory multi-core architecture, the underlying storage may support constant-time access. There are MapReduce implementations that target such environments, such as Phoenix [47,48], which is a shared-memory implementation of MapReduce for multi-core environments, and MARS [49,50], which accelerates MapReduce using graphics processors for coprocessing. In a similar vein, the Nornir run-time [51] offers an efficient multicore implementation of Kahn process networks [52], allowing the structuring of CPU-intensive computations as arbitrary communication graphs, which may contain cycles.…”
Section: Alternative and Hybrid Architecturesmentioning
confidence: 99%
“…Ten annotations are used to specify concurrency and synchronization; five are used to program MapReduce [22,61] computations.…”
Section: The Gossamer Approach and Contributionsmentioning
confidence: 99%